EVALUASI POTENSI INTERAKSI OBAT ANTIBIOTIKA PADA PENYAKIT INFEKSI GASTROINTESTINAL PASIEN RAWAT INAP PERIODE JANUARI – JUNI 2016 DI RUMAH SAKIT IBNU SINA MAKASSAR - Irma Santi; Hendra Herman; Andi Afifatun Nisa Al Ishak (Fakultas Farmasi UMI, 2020)
Infective gastrointestinal is gastrointestinal tract inflammation (GIT), which is caused by microorganisms. The symptoms include diarrhea, vomit, abdominal pain, and fever. This study aimed to determine the antibiotic drug interaction potential based on the interaction mechanisms of gastrointestinal infectious diseases of in patients in the period of January to June 2016 at IbnuSina Hospital Makassar and to determine the severity of antibiotic drug interaction using the website www.drugs.com on the gastrointestinal infectious diseases. This research is non experiments conducted by dekskriptif method retrospectively. The results showed that the drug interaction in the therapeutic use along with less potential antibiotics to interact. This was shown that pharmacokinetic interaction mechanism is 3.80% cases and pharmacodynamics interactions is 6.33% cases, while the pharmacokinetic interaction instead of antibiotics is 40.51% cases, and pharmacodynamics interactions is 7.60% cases. Based on the minor or moderate severity levels, the drug interactions between antibiotics and other drugs are 11.39% cases while the drugs which is not the antibiotics of drug interaction case is 32.91% cases.